Empresas, direitos humanos e gênero: desafios e perspectivas na proteção e na emancipação da mulher pelas empresas transnacionais - Cardia, Ana Cláudia Ruy (2014)
The present work aims to study the quantitative and qualitative expansion of transnational corporations as a result of the globalization process, as well as the consequent emergence of their responsibility for the protection and empowerment of women in this scenario. In this sense, an analysis of the main implications of this phenomenon for the Public International Law and the International Human Rights Law will be made, being critically assessed the international regulation of the activity developed by transnational corporations made by the subjects and actors that compose the post-modern international society in the issue of gender protection, in a context of necessary international cooperation between such entities. The present work is presented through bibliographical research as well as literature and documents of an exploratory-descriptive character, with the use of both inductive and deductive methods for achieving the main findings